BUSINESS MODEL ANALYSIS STUDY OF ADVENTURESTOCK.COM : VALUE-BASED APPROACH IN E-COMMERCE - Sembiring, Raja Agus Lukasta; Sembiring, Yasinta Aprilia (Multifinance, 2024)
This research aims to analyze the AdventureStock.com business model with a value-based approach in e-commerce, specifically in the value proposition, community involvement, sustainability, differentiation strategy, and customer satisfaction. This research uses a descriptive qualitative method with data collection techniques in the form of in-depth interviews, direct observation, and document analysis related to the AdventureStock.com platform. The data was analyzed using a thematic approach based on Prahalad and Ramaswamy's value co-creation theory and Osterwalder and Pigneur's business model elements. The results showed that AdventureStock.com has a unique value proposition by integrating the values of sustainability, community, and personal experience. The active involvement of the community in the value co-creation process increases product relevance and customer loyalty. The principle of environmental sustainability is applied as part of the core value, thus attracting customers who care about the environment. An effective differentiation strategy enables AdventureStock.com to occupy a niche market that many competitors have not yet touched. In addition, the focus on service personalization contributed significantly to customer satisfaction and built stronger long-term relationships with the user community. This study concludes that a value-based approach in e-commerce can create a competitive advantage and sustainable customer loyalty. These results are expected to serve as a reference for other e-commerce businesses in designing relevant and effective value-based strategies.